RuleSIM: a toolkit for simulating the operation and improving throughput of rule‐based spam filters. (5th July 2015) - Ruano‐Ordás, David; Fdez‐Glez, Jorge; Fdez‐Riverola, Florentino; Basto Fernandes, Vitor; Méndez, José Ramón
Summary: This paper introduces RuleSIM, a toolkit comprising different simulation tools specifically designed to aid researchers concerned about spam‐filtering throughput. RuleSIM allows easily designing, developing, simulating and comparing new scheduling heuristics using different filters and sets of e‐mails. Simulation results can be both graphically analysed, by using different complementary views, and quantitatively compared through several measures. Moreover, the underlying RuleSIM API can be easily integrated with third‐party Java optimization platforms to facilitate debugging and achieve better configurations for rule scheduling. RuleSIM is free software distributed under the terms of GNU Lesser General Public License, and both source code and documentation are publicly available athttps://github.com/rulesim/v2.0 . Copyright © 2015 John Wiley & Sons, Ltd.